High‐Throughput Assessments for Storage Stability, In Vitro Release, and Particle Size of Encapsulated Biocontrol Fungi in Hydrogel Beads. Issue 7 (6th July 2022) - Santos‐Díaz, Adriana; Uribe‐Gutiérrez, Liz; Cruz‐Barrera, Mauricio
Abstract: Use of biocontrol fungi (BF) such as Trichoderma spp. minimizes fungicide input and increases both plant nutrition and protection from disease. Thus, the introduction of BF by novel inoculants in crop management is an excellent strategy to promote sustainable antagonism activity. Within these strategies, encapsulation in polymeric matrices such as hydrogel beads will play a prominent role in providing an effective carrier/protector and long‐lasting bioproduct. These studies have used biomaterials with tunable physicochemical features, providing differential morphologies, compaction, and disintegration, among other parameters. Aiming at developing bioproducts within polymeric hydrogel beads, viability of encapsulated conidia, storage stability, release of active ingredient, and particle size are essential. However, there are no reports that detail standardized and comprehensive methods to evaluate the characterization of these bioproducts. We describe step‐by‐step protocols that go from sample preparation to testing the viability and storage stability using vacuum‐sealed aluminum foil bags. We also describe a high‐throughput in vitro method for quantifying released fungal conidia of BF at different pH values. Finally, the particle size of beads is established by bright‐field microscopy. These protocols could be transferable to other biological actives, accessible to researchers in the microbiology and bioengineering communities. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Viability of encapsulated conidia Basic Protocol 2 : Study of stability of prototypes under storage Basic Protocol 3 : Release profile of encapsulated conidia at different pH conditions Basic Protocol 4 : Determination of capsule size